The distinct O2 quenching mechanism between fluorescence and phosphorescence for dyes adsorbed on silica gel. Issue 46 (23rd November 2020) - Cheng, Yu-Hsuan; Belyaev, Andrey; Ho, Mei-Lin; Koshevoy, Igor O.; Chou, Pi-Tai
Abstract : In the solid phase, the lack of a solvent cage effect leads to the unstable CT states, rendering the decreased and thus a larger distinction between and, which therefore results in the efficient O2 quenching of fluorescence. Abstract : We herein aim to probe the emission quenched by O2 on silica gel. Our special focus is on the O2 quenching of the fluorescence of a series of organic D–π–A phosphonium compounds 1–3 . The results show that the O2 quenching rate constants for the fluorescence of 1–3 are on the order of 10 10 M −1 s −1, which are nearly on the same order as those measured for 1–3 and common organic compounds in solution. In yet another approach, the study of O2 quenching of phosphorescence in the solid phase indicates that the O2 quenching rate constant for the triplet state, i.e., , is smaller than by two orders of magnitude. Detailed investigation indicates that this distinction stems from the intrinsic O2 quenching rate constants for the singlet and triplet states subsequent to the formation of collisional complexes. In the absence of the solvent cage effect, is greatly influenced by the formation energy of the O2 –dye CT complex, whereas in the solid phase is a nearly diffusion-controlled rate. Due to the larger distinction between and in the solid phase, O2 quenching of fluorescence is efficient for dyes in the solid phase. This leads to a feasible application of sensing O2 with regular fluorescent dyes adsorbed on porous solid substrates.